CYBERCRIME COMPARISON UNDER CRIMINAL LAW IN SOME COUNTRIES - Andri Winjaya Laksana (Jurnal Pembaharuan Hukum, 2018)
Cybercrime has been become a major portion for law enforcement agencies and intelligence services to both national and international matter, development of information and technology’s crime resulted in every country have a different policy of criminalization. The emphasis on cross-country has made a crime on the internet is not just a national issue, but has become an International problem. therefore it is important to have uniformity in the prevention of cybercrime that this crime can be solved. Based on the comparison of cybercrime that included the rules from various countries including the United States, Singapore, the Netherlands, the Philippines, Myanmar as a reference in the application of criminal law enforcement regulations regarding cybercrime seal the document.